Stability and nutrients removal performance of a Phanerochaete chrysosporium-based aerobic granular sludge process by step-feeding and multi A/O conditions. (December 2021) - Cui, Lihui; Shen, Hao; Kang, Pengfei; Guo, Xiaoying; Li, Haisong; Wang, Yan; Wan, Junfeng; Dagot, Christophe
Highlights: Phanerochaete chrysosporium -based aerobic granular sludge (PC-AGS) was developed. PC-AGS greatly improved nutrients removal performance during 100 days operation. Increased extracellular proteins effectively promoted the stability of PC-AGS. Bacterial diversity inside granules was enhanced with the addition of fungal mycelial pellets. Abstract: A Phanerochaete chrysosporium -based aerobic granular sludge (PC-AGS) was developed by inoculating fungal mycelial pellets into a lab-scale aerobic granular sequencing batch reactor (AGSBR). A strategy using step-anaerobic feeding coupled with multi A/O conditions was adopted. The results showed that the removal efficiencies for total phosphorus (TP) and total inorganic nitrogen (TIN) were 94.56 ± 2.92% and 75.20 ± 7.74%, respectively, under relatively low aeration time. Compared with original AGS, the content of extracellular proteins for PC-AGS obviously increased from 18.61 to 41.44 mg/g MLSS by the end of phase I. Moreover, the mature granules had a larger size and better stability during the 100 days operation. Furthermore, the analysis of microbial diversity detected many key functional groups in PC-AGS granules that were beneficial to nutrients removal. This work demonstrated that the addition of fungal pellets not only enhanced the removal performance, but also improved the stability of the AGS system.